On the vertical variability of turbulent heat fluxes within and above a deciduous forest - Temple R. Lee; Sandip Pal; Praveena Krishnan; Tim B. Wilson; Rick D. Saylor; Tilden P. Meyers; John Kochendorfer; Will Pendergrass; Randy White; Mark Heuer (Agricultural and Forest Meteorology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Quantifying regulatory limits for multiple stressors in an open and transparent way - Rick J. Stoffels; Richard S. A. White (Conservation Biology, 2025)
Biodiversity is confronted globally by multiple stressors. Environmental policies must regulate these stressors to achieve targets, but how should that be done when the outcomes of limits on one stressor are contingent on other stressors, about which there is imperfect knowledge? Deriving regulatory frameworks that incorporate these contingencies is an emerging challenge at the science–policy interface. To be fit for implementation, these frameworks need to facilitate the inherently sociopolitical process of policy implementation and account transparently for uncertainty, such that practitioners and other stakeholders can more realistically anticipate the range of potential outcomes to policy. We developed an approach to quantify stressor limits that explicitly accounts for multistressor contingencies. Using an invertebrate data set collected over 30 years throughout New Zealand, we combined ecological and ecotoxicological models to predict biodiversity loss as a function of one stressor, treating multistressor contingencies as a form of uncertainty about the outcomes of limits on that stressor. We transparently accounted for that uncertainty by presenting regulatory limits as bands bounded between optimistic and pessimistic views that practitioners may have about the local context within which limits are applied. In addition to transparently accounting for uncertainties, our framework also leaves room for practitioners to build stakeholder consensus when refining limits to suit different local contexts. A criticism of this open, transparent approach is that it creates too much scope for choosing limits that are lenient on polluters, paralyzing on‐the‐ground management of multiple stressors, but we demonstrate that this is not necessarily the case.

On the application of the hockey-stick transition hypothesis to characterize turbulence within and above a deciduous forest - Temple R. Lee; Sandip Pal; Praveena Krishnan; Tim B. Wilson; Rick D. Saylor; Tilden P. Meyers; John Kochendorfer; Will Pendergrass; Randy White; Mark Heuer (Agricultural and Forest Meteorology, 2025)

Assigning trend‐based conservation status despite high uncertainty - Richard S. A. White; Rick J. Stoffels; Amy L. Whitehead (Conservation Biology, 2023)
Estimates of temporal trends in species’ occupancy are essential for conservation policy and planning, but limitations to the data and models often result in very high trend uncertainty. A critical source of uncertainty that degrades scientific credibility is that caused by disagreement among studies or models. Modelers are aware of this uncertainty but usually only partially estimate it and communicate it to decision makers. At the same time, there is growing awareness that full disclosure of uncertainty is critical for effective translation of science into policies and plans. But what are the most effective approaches to estimating uncertainty and communicating uncertainty to decision makers? We explored how alternative approaches to estimating and communicating uncertainty of species trends could affect decisions concerning conservation status of freshwater fishes. We used ensemble models to propagate trend uncertainty within and among models and communicated this uncertainty with categorical distributions of trend direction and magnitude. All approaches were designed to fit an established decision‐making system used to assign species conservation status by the New Zealand government. Our results showed how approaches that failed to fully disclose uncertainty, while simplifying the information presented, could hamper species conservation or lead to ineffective decisions. We recommend an approach that was recently used effectively to communicate trend uncertainty to a panel responsible for setting the conservation status of New Zealand's freshwater fishes.

Technology development for the early detection of plant pests: a framework for assessing Technology Readiness Levels (TRLs) in environmental science - Rehema White; Mariella Marzano; Elena Fesenko; Alan Inman; Glyn Jones; Barbara Agstner; Rick Mumford (Journal of Plant Diseases and Protection, 2022)
Innovation in environmental fields such as plant health is complex because of unbounded challenges and lack of certainty of commercial uptake. In this paper we present a Technology Readiness Level (TRL) framework, specifically to assist with assessment of technologies to support detection of tree pests and pathogens, but also for wider potential adaptation. Biosecurity can be enhanced by improved early detection of pests and pathogens, but development and deployment of new technologies requires robust scrutiny. We critically analyse the concept, practice and applicability of TRLs. Interviews revealed scientist perspectives during the development process of five novel early plant pest and pathogen detection technologies. A retrospective, collective narrative of one technology from concept to commercial deployment was undertaken. We then developed a calculator tool for assessment of biosecurity TRLs. Our findings illustrate the iterative process of technology development, the challenges in final TRLs of acquiring funding to move from proven success to viable product, inefficiencies created through the need for multiple projects for each technology and the imperative to consider the wider socio-ecological technical landscape, including policy context. End user engagement was particularly valuable at beginning and end of the TRL scale. We conclude that the TRL framework comprises a robust approach to assess technologies in that it facilitates progress tracking, evaluation of success likelihood and identification of opportunities for investment. However, its potential will only be realised for environmental management if it is integrated into the socio-ecological technical landscape and wider discussions regarding knowledge co-production and valuing nature.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Genome-wide screening for genetic loci associated with noise-induced hearing loss - Cory H. White; Jeffrey D. Ohmen; Sonal Sheth; Amina F. Zebboudj; Richard K. McHugh; Larry F. Hoffman; Aldons J. Lusis; Richard C. Davis; Rick A. Friedman (Mammalian Genome, 2009)

A shift in the habitat use pattern of a lentic galaxiid fish: an acute behavioural response to an introduced predator - Rick D. Stuart-Smith; Robert W. G. White; Leon A. Barmuta (Environmental Biology of Fishes, 2008)

A framework for predicting personal exposures to environmental hazards - James V. Zidek; Gavin Shaddick; Jean Meloche; Chris Chatfield; Rick White (Environmental and Ecological Statistics, 2007)

Species Identification of Tarantulas using Exuviae for International Wildlife Law Enforcement - Stephen D. Petersen; Tom Mason; Sarah Akber; Rick West; Brad White; Paul Wilson (Conservation Genetics, 2007)

Genomics of hybrid poplar ( Populus trichocarpa × deltoides ) interacting with forest tent caterpillars ( Malacosoma disstria ): normalized and full‐length cDNA libraries, expressed sequence tags, and a cDNA microarray for the study of insect‐induced defences in poplar - STEVEN RALPH; CLAIRE ODDY; DAWN COOPER; HESTHER YUEH; SHARON JANCSIK; NATALIA KOLOSOVA; RYAN N. PHILIPPE; DANA AESCHLIMAN; RICK WHITE; DEZENE HUBER; CAROL E. RITLAND; FRANÇOIS BENOIT; et al. (Molecular Ecology, 2006)
As part of a genomics strategy to characterize inducible defences against insect herbivory in poplar, we developed a comprehensive suite of functional genomics resources including cDNA libraries, expressed sequence tags (ESTs) and a cDNA microarray platform. These resources are designed to complement the existing poplar genome sequence and poplar ( Populus spp.) ESTs by focusing on herbivore‐ and elicitor‐treated tissues and incorporating normalization methods to capture rare transcripts. From a set of 15 standard, normalized or full‐length cDNA libraries, we generated 139 007 3′‐ or 5′‐end sequenced ESTs, representing more than one‐third of the c. 385 000 publicly available Populus ESTs. Clustering and assembly of 107 519 3′‐end ESTs resulted in 14 451 contigs and 20 560 singletons, altogether representing 35 011 putative unique transcripts, or potentially more than three‐quarters of the predicted c. 45 000 genes in the poplar genome. Using this EST resource, we developed a cDNA microarray containing 15 496 unique genes, which was utilized to monitor gene expression in poplar leaves in response to herbivory by forest tent caterpillars ( Malacosoma disstria ). After 24 h of feeding, 1191 genes were classified as up‐regulated, compared to only 537 down‐regulated. Functional classification of this induced gene set revealed genes with roles in plant defence (e.g. endochitinases, Kunitz protease inhibitors), octadecanoid and ethylene signalling (e.g. lipoxygenase, allene oxide synthase, 1‐aminocyclopropane‐1‐carboxylate oxidase), transport (e.g. ABC proteins, calreticulin), secondary metabolism [e.g. polyphenol oxidase, isoflavone reductase, (–)‐germacrene D synthase] and transcriptional regulation [e.g. leucine‐rich repeat transmembrane kinase, several transcription factor classes (zinc finger C3H type, AP2/EREBP, WRKY, bHLH)]. This study provides the first genome‐scale approach to characterize insect‐induced defences in a woody perennial providing a solid platform for functional investigation of plant–insect interactions in poplar.